Carcinogenic and anticancer activities of microbiota-derived secondary bile acids - Kouhzad, Mobina; Götz, Friedrich; Navidifar, Tahereh; Taki, Elahe; Ghamari, Mahsa; Mohammadzadeh, Roghayeh; Seyedolmohadesin, Maryam; Bostanghadiri, Narjess (Frontiers in Oncology, 2025)
Secondary bile acids (SBAs), which are metabolites produced by gut microbiota, have been implicated in both carcinogenic and anticancer processes. This review explores the dual role of SBAs, focusing on their molecular mechanisms and biological effects. The carcinogenic activities of SBAs include DNA damage, promotion of oxidative stress, and modulation of signaling pathways that drive tumorigenesis. Conversely, some SBAs exhibit anticancer properties by inducing apoptosis, inhibiting cell proliferation, and modulating immune responses. The article also discusses the complex interplay between SBAs and the host’s genetic and environmental factors, highlighting potential therapeutic implications and the need for targeted strategies to mitigate risks while harnessing beneficial effects. A comprehensive understanding of the delicate equilibrium between the deleterious and salutary impacts of SBAs has the potential to facilitate the development of innovative cancer prevention and treatment methodologies.